COMMUNITY EMPOWERMENT BY INCREASING KNOWLEDGE IN HANDLING EMERGENCIES AT HOME DURING THE COVID-19 PANDEMIC - Dhona Andhini; Hikayati Hikayati; Eka Yulia Fitri Y; Dian Wahyuni (Fakultas Kedokteran Universitas Sriwijaya, 2021)
The Covid-19 pandemic is still one of the causes of high morbidity and mortality rates worldwide, including in Indonesia. One of the causes of the high morbidity and mortality rates in Covid-19 sufferers is due to inappropriate treatment when self-isolated at home. This lack of care is due to a lack of public knowledge in caring for COVID-19 sufferers at home, especially for patients with comorbid diseases such as cardiovascular, gastrointestinal, and pulmonary diseases. Therefore, it is necessary to carry out a program to increase public knowledge to have a positive attitude in treating Covid-19 patients at home. Health education activity was conducted to provide and increase public knowledge about handling actions to overcome emergency conditions of cardiovascular, gastrointestinal, and pulmonary diseases during self-isolation at home. This activity was carried out online through the Zoom application and was attended by 72 participants. Public knowledge about handling emergency conditions of cardiovascular, gastrointestinal, or pulmonary disease in self-isolating patients at home still needs to be improved.